The etiological spectrum of bowel obstruction and early postoperative outcome among neonates at a tertiary hospital in Uganda - Nasser Kakembo; Paul Otim; Emmanuel Alex Elobu; Ronald Mbiine; David Komakech (World Journal of Pediatric Surgery, 2022)
Background Bowel obstruction is a common surgical emergency in newborns. One-fourth of neonates with obstruction suffer postoperative complications, with high mortality, especially in low-income countries. Factors attributed to mortality include prematurity, late presentation and associated multiple congenital anomalies. The prevalence and the predictors of mortality in our setting have not been well studied. We aimed to describe the early postoperative outcomes and to determine the predictors of mortality among neonates with bowel obstruction.Methods We conducted a prospective cohort study during 4 months, when we recruited postoperative neonates from the pediatric surgery unit of Mulago Hospital. We collected data on demographics, clinical presentations, maternal characteristics, the surgical procedure performed, postoperative outcomes, etc. After follow-up for 2 weeks, we analyzed the data using Cox proportional hazards regression models of predictors of mortality.Results A total of 76 neonates were recruited, with a male-to-female ratio of 2.2:1. The age ranged from 1 to 26 days, a median of 3 [interquartile range (IQR): 2, 7]. About 67.1% had birth weights ranging between 2.5 kg and 3.5 kg, a mean of 2.8 [standard deviation(SD)=0.64]; 76.3% were termed; with anorectal malformation (ARM), 31.6% as the leading cause, followed by jejunoileal atresia (JIA), 25%. Nearly 55.3% of neonates developed complications; 53.9% with post-operative fever, 15.8% had wound sepsis. The mortality rate was 44.7% (34/76) and was highest among cases of JIA, 41.2%. The predictors of mortality included prematurity, fever at admission, breastfeeding status, and mother’s parity as well as the cadre of healthcare providers (p<0.005).Conclusions ARM is the predominant cause of bowel obstruction among neonates, followed by JIA. The morbidity and mortality due to bowel obstruction among neonates are unacceptably high. The major predictors of mortality were prematurity, fever at admission, and the cadre of the healthcare providers.